Role of disulfide bonding in outer membrane structure and permeability in Chlamydia trachomatis. - Bavoil, P (1984)
The outer membrane of Chlamydia trachomatis can be efficiently solubilized by a variety of mild detergents in the presence of the reducing agent dithiothreitol. This allows purification of the chlamydial major outer membrane protein at high yield in very gentle conditions by using its differential solubility in Sarkosyl and octylglucoside in the presence of dithiothreitol. The major outer membrane protein of the L2 serovar is an acidic protein with a pI of ca. 5. It contains three cysteine residues that allow it to form a disulfide-linked proteinaceous network responsible for the characteristic rigid outer membrane of the elementary body. By the use of an in vitro reconstitution assay developed by Nikaido and his co-workers, it was shown that the outer membrane contains pores with an "exclusion limit" between molecular weights 850 and 2,250. In addition, the "opening-closing" of the pores was shown to be controlled through a simple reduction-oxidation mechanism. A model that outlines the role of disulfide bonding in the physiology of chlamydial development is presented.